1. Przekształć iloczyny na sumy.

a) 3(a-2)
b) -4(x+y)
c) -5(-x+1)
d) -3a(⅓-a)
e) (t-2s-1) × 7
f) ½(2a - 4b + 1)
g) m(2m+3)
h) 3p(2r + 5p -1)
i) xy(2x-3y+5)

2. Przekształć ilorazy na sumy.

a) (-4x+8):4
b) 5x+10y : 5
c) (6p² - 8pr) :(-2)
d) 3x - 6xy +1 : (-3)
e) (x² + x -1) :(-⅙)
f) 2,5x² - 0,5x + 1 : 5

1

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-15T18:00:04+01:00
1.
a) 3(a-2)=3a-6
b) -4(x+y)=-4x-4y
c) -5(-x+1)=5x-5
d) -3a(⅓-a)=-a+3a²
e) (t-2s-1) × 7=7t-14s-7
f) ½(2a - 4b + 1)=a-2b+½
g) m(2m+3)=2m²+3m
h) 3p(2r + 5p -1)=6pr+15p²-3p
i) xy(2x-3y+5)=2x²y-3xy²+5xy

2.
a) (-4x+8):4=-x+2
b) 5x+10y : 5=x+2y
c) (6p² - 8pr) :(-2)=3p²4pr
d) 3x - 6xy +1 : (-3)=-x+2xy-⅓
e) (x² + x -1) :(-⅙)=-6x²+6x+6
f) 2,5x² - 0,5x + 1 : 5 =0,5x²-0,1x+⅕